The Modified Richardos Equation for Assessing the Impact of Drought and Salinity in Arid and Semi-Arid Zones. Part Two A Soil Hydraulic Capacitance (Global Journal of Science Frontier Research, 2023)
A soil hydraulic capacitance is a new physical property related to the interactions between the agro eco-system components soil water plant and atmosphere It gives new quantitative details about the processes control the plant water uptake ascending of sap and soil response toward the root water uptake under a certain soil moisture regime and climatic changes The soil hydraulic capacitance a tank like a plant water reservoir is being controlled by signals valves like switches Three types of signaling devices Geo Bio and weather controlled were discussed The soil hydraulic capacitance property was first discovered by the author when modeling the wheat root water uptake under saline and drought conditions Under the latter extreme conditions treating plants with silica products was the managerial practice used for enhanced plant growth and water uptake A split-split plot experimental design with four replicates was used to conduct the research in Oraby Village Maryout area Alexandria Egypt in the last year of the most water-scarce decade The aim of the experiment was to put the sink source term of Richard s equation S into investigation under a macroscopic electrical modeling AMUN_SHC Natural drought and salinity stressors are the abiotic extremes Silicon foliar applications are the managerial practices used for combating the latter extremes The Plant stress index soil stress index and strain of straw sap were calculated The S-shaped relative extreme response function was used to describe the SSI f h z t the effect of silicon as a beneficial element on the soil hydraulic capacitance and therefore the winter wheat water uptake was estimated and discussed The soil hydraulic capacitance equations were derived and discussed The brilliant result from the research is that the soil hydraulic capacitance a recently discovered soil hydro-physical property controls the root water uptake under drought and saline conditions in accordance with stress strain and weathered controlled relationships
Keywords: soil hydraulic capacitance; drought and salinity stresses; strain; compensated water uptake